The Architecture of Intellegent Transportation System based on Sensor Monitoring (Implementation in Jakarta Area) - Handoko, Melyani; Mubarok, Husni; Shaura, Rizkiana Karmelia; Lesmana, Hendra; Widyastuti, Reni; Swastika, Rahayu; Haryanto, Wawan; Hartini, Dorit (Journal of Technology Informatics and Engineering, 2025)
Urban congestion and traffic inefficiencies pose significant challenges for developing cities such as Jakarta. Conventional traffic management systems often lack responsiveness and integration, leading to time delays, fuel wastage, and safety hazards. This study proposes the architecture of an Intelligent Transportation System (ITS) based on sensor monitoring as a solution to improve vehicle flow, surveillance, and timeliness within urban transportation networks. The objective is to develop a sensor-based ITS framework capable of real-time monitoring and decision-making through the integration of motion, ultrasonic, PIR (Passive Infrared), and speed sensors. The proposed system was simulated in the Jakarta metropolitan context, focusing on its feasibility and performance under dense traffic scenarios. The results demonstrate that the incorporation of four monitoring technologies—RFID, embedded sensors, IP address tracking, and QR barcode scanning—can significantly enhance the efficiency of traffic control. The framework enables vehicle surveillance, automated violation ticketing, and optimized travel time estimation. It also proposes a comprehensive four-layer surveillance system encompassing traffic, vehicle, passenger, and driver monitoring. This study contributes to the development of smart city infrastructure by offering a scalable ITS model that minimizes congestion, supports automated law enforcement, and enhances public transportation accessibility through digital integration. The findings serve as a baseline for future implementation and technological expansion of ITS in other congested urban regions.